1986
DOI: 10.1021/ja00285a014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of benzene by a tetrakis(trimethylphosphine)osmium(II) system. Mechanism of activation

Abstract: The intermolecular activation of the carbon-hydrogen bond in benzene has been investigated by the thermolysis of c;í-L4Os(H)R (L = P(CH3)3; R = CH3, 1; R = CH2C(CH3)3, 2; R = CH2Si(CH3)3, 3). Thermolysis of 2 at 70 °C in benzene results in activation of the arene C-H bonds to afford L4Os(H)(C6H5), 6, quantitatively. This reaction is shown to proceed, in the case of 2, via initial reversible L dissociation to form an unsaturated intermediate, L3Os(H)Np, 9, which is configurationally stable during its lifetime a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Therefore, the attempt on direct formation of styrene from benzene and ethylene using aromatic C-H bond activation leading to C-C bond formation is a considerably attractive field, which has enough room to be developed from the industrial point of view. As described in Section 1, much work related to homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Group VIII metal complexes can also be employed for olefin oxidation reactions such as Pd-catalyzed partial oxidation of ethylene, as is done in the well-known Wacker reaction to form acetaldehyde [61,62] and oxidative vinylation of acetic acid to produce vinyl acetate [63].…”
Section: Conventional Synthesis Of Styrenementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the attempt on direct formation of styrene from benzene and ethylene using aromatic C-H bond activation leading to C-C bond formation is a considerably attractive field, which has enough room to be developed from the industrial point of view. As described in Section 1, much work related to homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Group VIII metal complexes can also be employed for olefin oxidation reactions such as Pd-catalyzed partial oxidation of ethylene, as is done in the well-known Wacker reaction to form acetaldehyde [61,62] and oxidative vinylation of acetic acid to produce vinyl acetate [63].…”
Section: Conventional Synthesis Of Styrenementioning
confidence: 99%
“…Significant efforts have been directed at homogeneous C-H bond activation of aromatic compounds by discrete transition metal complexes [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. However, among the numerous stoichiometric studies, relatively small numbers of organic syntheses are reported.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described the conversion of the bromo complexes Cp * Os(P-P) 2 Br to their corresponding hydrides Cp * Os(P-P)H, where P-P = bis(dimethylphosphino)methane (dmpm), dppm = bis(diphenylphosphino)-methane (dppm), or 1,2-bis(dimethylphosphino)ethane (dmpe) [16]. Treatment of these hydride complexes with one to two equivalents of methyl trifluoromethanesulfonate in pentane results in loss of methane and generation of the triflate compounds Cp * Os(dmpm)(OTf) (1), Cp * Os(dppm)-(OTf) (2), and Cp * Os(dmpe)(OTf) (3), in 59%, 69%, and 86% yield, respectively.…”
Section: Synthesis Of Triflate Compoundsmentioning
confidence: 99%
“…Treatment of these hydride complexes with one to two equivalents of methyl trifluoromethanesulfonate in pentane results in loss of methane and generation of the triflate compounds Cp * Os(dmpm)(OTf) (1), Cp * Os(dppm)-(OTf) (2), and Cp * Os(dmpe)(OTf) (3), in 59%, 69%, and 86% yield, respectively. To obtain high yields of these compounds, it is important to limit the amount of MeOTf added and to isolate the reaction products promptly (i.e., after at most a few hours).…”
Section: Synthesis Of Triflate Compoundsmentioning
confidence: 99%
See 1 more Smart Citation